Transcranial Direct Current Stimulation of the Medial Prefrontal Cortex Affects Judgments of Moral Violations - Yuan, Hong; Tabarak, Serik; Su, Wenxin; Liu, Yong; Yu, Jing; Lei, Xu (Frontiers in Psychology, 2017)
Previous studies show that neural activities in the medial prefrontal cortex (mPFC) are correlated with moral processing during picture viewing tasks. In this study, we applied transcranial direct current stimulation (tDCS) to determine whether this non-invasive brain stimulation technique could modulate the evaluation of moral violations. Sixty-four subjects were randomly recruited, separated into different groups and tested with 42 pairs of pictures depicting moral violations. Each subject was required to rate the pictures two separate times, i.e., before and after tDCS intervention. We found that anodal tDCS (atDCS) increases cortical excitability over the mPFC (between the Fpz and Fp1 positions) as well as the sense of morality and emotional arousal of the subjects. In conclusion, this study indicated that the mPFC plays an important role in moral judgments while modulating ratings of moral violations under tDCS intervention conditions.